Electrocatalytic Reduction of Carbon Dioxide with a Well‐Defined PN3−Ru Pincer Complex. Issue 2 (13th November 2015) - Min, Shixiong; Rasul, Shahid; Li, Huaifeng; Grills, David C.; Takanabe, Kazuhiro; Li, Lain‐Jong; Huang, Kuo‐Wei
Abstract: A well‐defined PN 3 −Ru pincer complex (5 ) bearing a redox‐active bipyridine ligand with an aminophosphine arm has been established as an effective and stable molecular electrocatalyst for CO2 reduction to CO and HCOOH with negligible formation of H2 in a H2 O/MeCN mixture. Abstract : Done in a pince : A PN 3 −Ru pincer complex (see figure) has been found to show high activity and stability as a molecular electrocatalyst for CO2 reduction to CO and HCOOH in MeCN/H2 O.